(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
In the midst of dual pandemics, the racial justice uprising and the Coronavirus pandemic, I, a black associate professor of education, took on the challenge of having my white colleague as an apprentice for racial justice work. While co-teaching a critical diversity course, I decided to strategically engage our College of Education in a robust conversation on racial equity and reconciliation. An unanticipated event in that process was that my apprentice would become an effective ally and co-conspirator. I share this insight of our process in hopes that aspiring allies might improve their effort.